Epirubicin: a new entry in the list of fetal cardiotoxic drugs? Intrauterine death of one fetus in a twin pregnancy. Case report and review of literature. Issue 1 (December 2015) - Framarino-dei-Malatesta, Marialuisa; Perrone, Giuseppina; Giancotti, Antonella; Ventriglia, Flavia; Derme, Martina; Iannini, Isabella; Tibaldi, Valentina; Galoppi, Paola; Sammartino, Paolo; Cascialli, Gianluca; Brunelli, Roberto
Abstract Background Current knowledge indicate that epirubicin administration in late pregnancy is almost devoid of any fetal cardiotoxicity. We report a twin pregnancy complicated by breast cancer in which epirubicin administration was causatively linked to the death of one twin who was small for gestational age (SGA) and in a condition of oligohydramnios and determined the onset of a transient cardiotoxicity of the surviving fetus/newborn. Case presentation A 38-year-old caucasic woman with a dichorionic twin pregnancy was referred to our center at 20 and 1/7 weeks for a suspected breast cancer, later confirmed by the histopathology report. At 31 and 3/7 weeks, after the second chemotherapy cycle, ultrasound examination evidenced the demise of one twin while cardiac examination revealed a monophasic diastolic ventricular filling, i.e. a diastolic dysfunction of the surviving fetus who was delivered the following day due to the occurrence of grade II placental abruption. The role of epirubicin cardiotoxicity in the death of the first twin was supported by post-mortem cardiac and placental examination and by the absence of structural or genomic abnormalities that may indicate an alternative etiology of fetal demise. The occurrence of epirubicin cardiotoxicity in the surviving newborn was confirmed by the report of high levels of troponin and transient left ventricular septal hypokinesia. Conclusion Based on our findings we suggest that epirubicin administration in pregnancy should be preceded by the screening of some fetal conditions like SGA and oligohydramnios that may increase its cardiotoxicity and that, during treatment, the diastolic function of the fetal right ventricle should be specifically monitored by a pediatric cardiologist; also, epirubicin and desamethasone for lung maturation should not be closely administered since placental effects of glucocorticoids may increase epirubicin toxicity.